Macrophage Targeting: Comparative Cytotoxicity Activity of Imipramine-loaded Polymeric Nanoparticles and Niosomes - Veintramuthu, Sankar (Asian Journal of Pharmaceutics (AJP), 2024)
The aim of the present study was to prepare niosomal and nanoparticle formulations for drug therapy of leishmaniasis. Imipramine, an antidepressant, is reported to have anti-leishmaniasis activity in the dose of 5–10 mg/kg. Materials and Methods: In this study, we tried an approach with imipramine and polymer chitosan to target mannose receptors on macrophages using nanoparticles as drug carrier and with span 40 as surfactant in niosomes. Formulation of niosomes encapsulated with imipramine was optimized by changing the proportions of span 40, cetrimide, and cholesterol. The imipramine encapsulated niosomal formulations based on span 40, cetrimide, and cholesterol was prepared by hand shaking method and characterized using atomic force microscopy. The nanoparticles were prepared by modified ionic gelation method, where chitosan was conjugated with mannose for facilitation of uptake by macrophages. Results: The Atomic Force Microscopy results showed that the particles were spherical in shape and had a size between 200 and 900 nm. The prepared nanoparticles were evaluated for particle size, encapsulation efficiency and in vitro drug release. The in vitro release of nanoparticles shows 76 ± 1% release in 6 h. Conclusion: Niosomes and nanoparticles cell uptake studies were evaluated using RAW 264.7 cell lines. The % viability values for niosomes and nanoparticles were 42.53% and 70.17% at the highest concentration of 100 μg/mL after the incubation period of 24 h, respectively.